The mechanical and microstructural response of single crystal aluminium to one dimensional shock loading: The effects of orientation. (1st March 2023) - Millett, J.C.F.; Fensin, S.J.; Owen, G.D.; Eftink, B.P.; Lear, Calvin; Whiteman, G.; Gray, G.T.
Abstract: A series of plate impact experiments have been performed on the three principal orientations of single crystal aluminium: [100], [110] and [111]. Experiments were designed to probe the Hugoniot Elastic Limit, spall strength and Equation of state as well as understand the microstructural response, via transmission electron microscopy, Transmission Kikuchi Diffraction and mechanical testing of shocked material. Results from this work, show that orientation affects the HEL and spall strength in a similar manner to the quasi-static uniaxial stress compressive response, with [100] and [110] being similar and [111] significantly stronger. This correlates with expectations from considerations using the Schmid analysis. However we have noted that similar studies in copper yield a different ordering of the HELs. We have reconciled those differences using an analysis based on second order elastic constants. However the shocked microstructures and post shock quasi-static mechanical response are strongly influenced by orientation. The [100] orientation shows a response typical of high stacking fault face centred cubic metals, consisting of equiaxed subgrains and a strong post shock hardening during quasi-static mechanical testing, similar to results in polycrystalline aluminium. In contrast, the [110] and [111] orientations have a microstructural response more similar to polycrystalline aluminium after repeated shock loading excursions, combined with much lower post shock hardening during mechanical testing. This suggests that these orientations require much greater dislocation activity to achieve the same plastic deformation as [100]. This would appear to agree with the much higher degree of work hardening observed in these orientations compared to [100]. Graphical abstract: Image, graphical abstract